The construction of a formal model of an information object in digital library - Novytskyi, Oleksandr (Видавництво Львівської політехніки, 2013)
The article presents a model of a digital library informational object that aims to preserve and provide access to scientific resources. As a formal representation a UML class diagram is used, to identify semantic and logical contradictions in this diagram is proposed to express it by means of description logic.
Keywords: digital libraries; information model object; description logic